The Cambridge handbook of U.S. labor law for the twenty-first century / edited by Richard Bales, Charlotte Garden. - Bales, Richard A.; Garden, Charlotte (Cambridge University Press, 2020)
Over the last fifty years in the United States, unions have been in deep decline, while income and wealth inequality have grown. In this timely work, editors Richard Bales and Charlotte Garden - with a roster of thirty-five leading labor scholars - analyze these trends and show how they are linked. Designed to appeal to those being introduced to the field as well as experts seeking new insights, this book demonstrates how federal labor law is failing today's workers and disempowering unions; how union jobs pay better than nonunion jobs and help to increase the wages of even nonunion workers; and how, when union jobs vanish, the wage premium also vanishes. At the same time, the book offers a range of solutions, from the radical, such as a complete overhaul of federal labor law, to the incremental, including reforms that could be undertaken by federal agencies on their own.